Kendala dan Miskonsepsi Kognitif Siswa dalam Menyelesaikan Soal Geometri Tingkat Tinggi (HOTS) - Lastri Hutagalung; Lukita Ambarwati; Anny Sovia; Tian Abdul Aziz; Flavia Aurelia Hidajat (FKIP Universitas Mataram, 2025)
This study aims to identify students’ misconceptions in solving Higher Order Thinking Skills (HOTS) geometry problems on plane figures. A descriptive qualitative approach using Cognitive Error Analysis was applied to the written responses of 10 eleventh-grade students in the Mathematics Cambridge Program. The validated instrument consisted of three HOTS essay items. Data were analyzed through error classification, mapping to HOTS levels (C4, C5, C6), and in-depth diagnosis of responses identified as misconceptions. The findings show that students’ main difficulties lie in the Analyzing stage (C4), which subsequently weakens their ability to evaluate and create strategies (C5–C6). Two dominant patterns emerged: misreading non-routine instructions and errors in fundamental geometric concepts, with several cases indicating independent weaknesses at C6. These results highlight the need to strengthen strategic analysis as the foundation for HOTS development. The study is limited by its small sample size and reliance on written data.